The implementation of forensic accounting and investigative audit in the BPKP of East Nusa Tenggara Province - Afdil Galang Pamungkas; Daniel Sugama Stephanus (STIE Perbanas Surabaya, 2018)
This study aims to explore and analyze (1) the effect of the implementation of forensic accounting on fraud prevention; (2) the effect of the implementation of forensic accounting on fraud detection; and (3) the effect of the implementation of investigative audit on fraud disclosure in regional fi nancial management. The research method used in this study is descriptive qualitative method that examines some information derived from informants through in-depth interview. The results of the research analysis show that there are some problems or weaknesses in the implementation of forensic accounting, such as uneven SPIP maturity level, employees of agencies that are resistant to FCP implementation, the implementation of SIMDA that is not maximal, the absence of EDP laboratories in the BPKP of East Nusa Tenggara, and discrepancies in budget estimates on the implementationof the probity audit. In addition, there are weaknesses in the implementation of investigative audits, where fraud disclosure in the BPKP is based solely on request.